2015
DOI: 10.2174/1568026615666150827094652
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms and Rational Design of Anti-Diabetic Vanadium Compounds

Abstract: Vanadium compounds are promising anti-diabetic agents. Although BEOV was not able to succeed in phase II clinical trial, great progresses have been made in the past three decades on the discovery and development of anti-diabetic vanadium compounds. A vast of knowledge has been obtained on the molecular mechanisms of both the pharmacological and toxicological effects of vanadium complexes. It has been revealed that vanadium compounds exert insulin enhancement effects and cell protection via a multiple mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
0
20
1
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11] Furthermore, the antidiabetic, anti-virus, anti-bacterial and anti-tumor activities of V 10 and vanadate compounds are attracting increasing interest. [12][13][14][15][16][17][18] Decavanadate also exhibits insulin-mimetic behavior, and it was shown that, upon incubation with decavanadate, rat adipocytes accumulate much more glucose than with well-established mimetic agents such as BMOV. 18 Decavanadate is in many cases likely a pro-drug, inducing anti-diabetic activity through peroxovanadate production.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Furthermore, the antidiabetic, anti-virus, anti-bacterial and anti-tumor activities of V 10 and vanadate compounds are attracting increasing interest. [12][13][14][15][16][17][18] Decavanadate also exhibits insulin-mimetic behavior, and it was shown that, upon incubation with decavanadate, rat adipocytes accumulate much more glucose than with well-established mimetic agents such as BMOV. 18 Decavanadate is in many cases likely a pro-drug, inducing anti-diabetic activity through peroxovanadate production.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we believe that programmed cell death is not the mechanism responsible for the cytotoxic activity of both compounds. As the caspase‐3 expression was not modified it is unlikely that anoikis nor intrinsic or extrinsic apoptosis are responsible for the cell death induced by both compounds; it is possible that this is the consequence of MCL1 stabilization as both compounds exert an insulin mimetic effect mediated by the secretion of insulin growth factor (Galluzzi, Lopez‐Soto, Kumar, & Kroemer, ; Leon et al, ; Niu et al, ; Pessoa, Etcheverry, & Gambino, ). Interestingly, caspase‐1 expression decreased in all the experimental design, so pyroptosis can hardly be considered as responsible for the A549 cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The most important biological valences are III, IV and V (Barceloux, 1999). However, the majority of them exhibit insulin-like effects (Niu et al, 2016), but most significantly, several vanadium compounds prevent and inhibit the growth of various types of cancer in multiple in vitro and in vivo assays (Kowalski, Hac, Wyrzykowski, Zauszkiewicz-Pawlak, & Inkielewicz-Stepniak, 2017;Leon et al, 2015). Their cytotoxic effect (Rivadeneira et al, 2010;Zwolak, 2015), disruption of cellular signal transduction pathways, cell cycle arrest and apoptosis effect is apparently mediated by the generation of reactive oxygen species (ROS); however, these effects are valence dependent (Liao et al, 2013;Rozzo et al, 2017;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Особый интерес вызывает возможность использования ванадия в комплексной терапии сахарного диабета [17]. При этом активно разрабатываются и тестируются различные неорганические и органические соединения ванадия [18,19]. Одним из условий фармакологической эффективности соединений ванадия является возможность их трансформации в соответствующие комплексы оксида ванадия (IV) при физиологических значениях pH [20].…”
Section: ванадий в терапии сахарного диабетаunclassified